Effect of hydroxytyrosol on quality of sulfur dioxide-free red wine. (1st February 2016) - Raposo, R.; Ruiz-Moreno, M.J.; Garde-Cerdán, T.; Puertas, B.; Moreno-Rojas, J.M.; Gonzalo-Diago, A.; Guerrero, R.F.; Ortiz, V.; Cantos-Villar, E.
Highlights: Hydroxytyrosol-enriched products were evaluated as an alternative to sulfur dioxide in red wine. Enological parameters and volatile composition were hardly modified. Wines sensory analysis showed differences among wines. These differences could by justified by wine olfactometric profile. The key point of the process seems to be the evolution during the storage in bottle. Abstract: In this work, the feasibility of two commercial products enriched in hydroxytyrosol (HT) as alternative to sulfur dioxide in Syrah red wines was evaluated. The HT enriched products came from synthesis and from olive waste. Wines treated with HT were compared with wines treated with sulfur dioxide at two winemaking stages: bottling and after 6 months of storage in bottle. Minor differences were found in enological parameters and volatile composition (esters, alcohols and acids). Significant differences were observed in color related parameters and sensory analysis. HT wines improved color parameters as well as scents and tasting at bottling. However, after 6 months of storage in bottle HT wines were more oxidized than SO2 wines. The olfactometry profile of HT wines supported sensory analysis. HT wines showed new odorant zones from both the added product and oxidation.